2002
DOI: 10.1016/s0272-6963(02)00040-2
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the dark side of worker flexibility

Abstract: Flexible work assignment has great potential to increase productivity. When bottlenecks develop, for example, downstream operations may halt for lack of materials. A flexible worker can prevent this by moving in and increasing capacity temporarily, thereby avoiding work stoppages. In practice, it is not that simple. This paper identifies several “negative side effects” that occur in systems that rely on worker flexibility, effects that may partially or totally offset the advantages. Research has shown that per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
96
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 23 publications
5
96
2
1
Order By: Relevance
“…The involvement of nonexperts also is an important opportunity to engender pro-nature behavior change: appropriately framed information and involvement in a process of developing a strategy to achieve a mutually desired state-the vision-can rapidly change people's norms (62,74,75). It forces them to confront realities about unsustainable futures that will be harmful to themselves and their offspring and to contribute by exploring possible solutions to these problems (72,(75)(76)(77).…”
Section: Operational Modelmentioning
confidence: 99%
“…The involvement of nonexperts also is an important opportunity to engender pro-nature behavior change: appropriately framed information and involvement in a process of developing a strategy to achieve a mutually desired state-the vision-can rapidly change people's norms (62,74,75). It forces them to confront realities about unsustainable futures that will be harmful to themselves and their offspring and to contribute by exploring possible solutions to these problems (72,(75)(76)(77).…”
Section: Operational Modelmentioning
confidence: 99%
“…Specialization is also valuable as it limits worker distractions due to task change (Schultz, McClain and Thomas 2003;Staats and Gino 2011). Psychology research shows that when a worker switches to a different task it is necessary to load the steps to complete the task into her working memory (Rubinstein, Meyer and Evans 2001).…”
Section: Focal and Related Experience At The Individual Levelmentioning
confidence: 99%
“…Changing tasks at hand necessitates changing the primary task set in her working memory (Monsell 2003). Prior work finds that there is an absolute cost to task change because individuals must go through a cognitive setup to prepare to execute the next task (Schultz et al 2003;Staats and Gino 2011). More importantly, prior task sets may have an ongoing negative effect on performance (Allport et al 1994;Allport and Wylie 1999).…”
Section: Sub-task Varietymentioning
confidence: 99%
“…In examining work sharing in factory assembly lines, Schultz and colleagues (2003) cautioned that the behavioral effects of cross-training can reduce or even eliminate its potential benefits. [46] Similarly, some of the nurses indicated that cross-training was a source of stress and increased their professional clinical responsibility to the College of Nurses of Ontario (regulatory body in the province of Ontario, Canada). Indeed, given the already elevated workloads [47] that nurses experience, cross-training may place an additional burden on nurses' health and wellbeing.…”
mentioning
confidence: 99%
“…Many of the potentially negative impacts stem from thoughtless implementations of cross-training. [46] At the hospital where cross-training occurred (Sudbury, Ontario, Canada), there was a high rate of staff turnover with the implementation of cross-training at some hospital sites. Some felt that nurses had to take more time off of work in terms of sick days because of the physical and mental demands of the workplace.…”
mentioning
confidence: 99%